Victimization of the Substance Abuse and Sexual Behaviors among Junior High School Students in Cambodia - Yat YEN; Yumin SHI; Bunly SOEUNG; Rathny SUY; Muhammad Tayyab SOHAIL (Tehran University of Medical Sciences, 2018)
Background: We examined the current prevalence of substance abuse and sexual behaviors among junior high school students and the relationships between substance abuse, sexual behaviors, and victimization using multiple mediations. Methods: Overall, 1703 junior high school students from the 2013 Cambodia Global School-based Health Survey were selected for the study. The descriptive statistics were performed in IBM SPSS to determine the prevalence of substance abuse, sexual behaviors, and victimization. The Process Macro was installed in Regression of the SPSS to test the hypotheses and mediations. Results: The majority of students who used alcohol (15.4%), drugs (3.05%), and had sexual intercourse (12.45%), were male aged 14-15, and in grade 7. These students were very vulnerable to many risky behaviors, including bullying (22.20%), physical attacks (20.96%) and fights (14.50%), unintentional accidents (21.32%), and suicidal attempts (5.05%). All three hypotheses were significantly supported. Of the potential mediators examined, drug use is the most important mediator. Conclusion: The substance abuse and reproductive health are national problems, but abusive behaviors among students are of particular concern. Explicit policies and awareness programs of such problems at the high school level need to be made and called for public participation, particularly the school authorities and parents.